RISK MANAGEMENT STRATEGIES FOR MICROFINANCE BANKS IN NIGERIA: A CREDIT RISK FOCUS - Ehiogu Chizoba Perpetua; Kologa Inebimowei Freedom (Gusau Journal of Accounting and Finance)
This study, Risk Management Strategies for Microfinance Banks in Nigeria with a Credit Risk Focus, explores the critical role of credit risk management in sustaining capital adequacy and promoting financial stability among Nigerian microfinance banks a sector fundamental to financial inclusion but often overlooked in mainstream banking research. Drawing on a comprehensive 19-year dataset (2005-2023), the study empirically investigates the effects of three key credit risk mitigation instruments: Loan Loss Reserves, Collateralization, and Credit Insurance. Using advanced econometric techniques, including cointegration analysis and the Vector Error Correction Model (VECM), the findings reveal that Loan Loss Reserves and Collateralization significantly influence capital adequacy in the short term, while Credit Insurance demonstrates both short-term and long-term effects, making it an essential tool for sustained financial stability. By focusing specifically on microfinance institutions rather than commercial banks, the study addresses a critical gap in the literature and regulatory discourse. The results highlight the importance of strengthening reserve provisioning frameworks, minimizing over-reliance on collateral through diversified credit risk assessments, and expanding the adoption of credit insurance to reduce default exposure and enhance solvency. Furthermore, the study emphasizes the integration of credit risk practices into broader institutional and regulatory mechanisms aimed at reinforcing both capital adequacy and the financial stability of the microfinance sector. The research contributes to theory by applying the Financial Stability Hypothesis within the microfinance context and offers actionable insights to policymakers and financial institutions seeking to build a more resilient, inclusive banking system.